2020
DOI: 10.31616/asj.2019.0124
|View full text |Cite
|
Sign up to set email alerts
|

Endplate Changes with Polyetheretherketone Cages in Posterior Lumbar Interbody Fusion

Abstract: Study Design: A retrospective radiographic analysis.Purpose: The aim of the current study is to assess endplate changes after the use of polyetheretherketone (PEEK) cages in posterior lumbar interbody fusion (PLIF).Overview of Literature: A few recent reports had revealed endplate abnormalities due to PEEK cages, which may lead to nonunions.Methods: A retrospective computed tomography (CT)-based analysis of the endplate cavities and fusion status following PLIFs with PEEK cages was conducted by two independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Posterior lumbar interbody fusion (PLIF) is a well-proven procedure to perform in patients who require stabilization following wide decompression for spinal stenosis or spondylolisthesis [1,2]. PLIF involves cage insertion through the disc space.…”
Section: Introductionmentioning
confidence: 99%
“…Posterior lumbar interbody fusion (PLIF) is a well-proven procedure to perform in patients who require stabilization following wide decompression for spinal stenosis or spondylolisthesis [1,2]. PLIF involves cage insertion through the disc space.…”
Section: Introductionmentioning
confidence: 99%
“…Although autologous bone is considered the gold standard bone graft material, it is well known to be associated with several graft site morbidities, such as pain, hematoma formation, infection, and pelvic fracture [ 22 , 23 ]. BMP has been widely utilized to increase fusion potential in various spinal fusion surgeries [ 24 , 25 ]. Although several previous studies have reported no significant difference in acute complications and malignancy risk between pediatric patients treated with and without BMP, complications such as wound infections, seromas, and heterotopic bone development have also been reported [ 26 , 27 , 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, rhBMP-2 has emerged as a good substitute for auto-iliac bone graft in spinal fusion surgeries. However, the use of rhBMP-2 in fusion surgery has side effects such as heterotrophic ossification, radiculitis, and end plate changes [14,[18][19][20]. In spite of the dosage-dependent side effects, rhBMP-2 has been widely utilized off-label without a defined dose.…”
Section: Discussionmentioning
confidence: 99%